EKSPLORASI PENGARUH BEAUTY INFLUENCER DAN CUSTOMER TRUST TERHADAP PURCHASE INTENTION PADA PRODUK AZARINE DI MEDIA SOSIAL TIKTOK - Dewi, Ni Komang Teni Shintya; Prawitasari, Putu Putri; Lestari , Ni Putu Nina Eka (Jurnal Bina Bangsa Ekonomika, 2025)
Indonesian people use social media with high intensity. Since social media is a platform for sharing information, buying and selling sites, and communication, the number of people using it is currently increasing. TikTok is one of the most popular social media sites today. The use of  beauty influencers to market and promote Azarine products on TikTok social media is one of the new developments that have emerged as a result of the high effectiveness of digital marketing. Customer Trush towards their purchase intention is greatly influenced by beauty trends pioneered by  beauty influencers. The purpose of this study was to examine how Customer Trush and influencer appeal  affect purchase intent. Social media users on TikTok who have used Azarine products are the research population. Purposive sampling combined with a non-probability sampling approach was used to select samples for this study. Quantitative research is the methodology used, and questionnaires are distributed to collect data. The SPSS version 25 program was used to analyze the data in this study using a multiple linear regression approach. The results of the study show that: (1) Beauty Influencers have a positive and significant influence on Purchase Intention; (2) Purchase Intention is positively  and significantly influenced by Consumer Trust; and (3) Purchase Intention is positively  and significantly influenced by Beauty Influencer and Consumer Trust